MO098HUMAN STOOL METABOLOME DIFFERS UPON 24-HOUR BLOOD PRESSURE LEVELS AND THE NON-DIPPING BLOOD PRESSURE PROFILE. (29th May 2021) - Huart, Justine; Cirillo, Arianna; Taminiau, Bernard; Descy, Julie; Saint-Remy, Annie; Daube, Georges; Krzesinski, Jean-Marie; Melin, Pierrette; De Tullio, Pascal; Jouret, François
Abstract: Background and Aims: Dysbiosis of gut microbiota (GM) has been involved in the pathophysiology of arterial hypertension (HT), via a putative role of food-derived short chain fatty acids (SCFAs). Among the clinical manifestations of HT, the absence of a significant drop in blood pressure (BP) overnight (i.e. non-dipping BP profile) has been associated with poor cardiovascular outcomes. The link between GM and non-dipping BP profile is unknown. Method: After informed consent, 16 male patients and their female partners (n=10) were subjected to 24-hours ambulatory BP monitoring and were categorized in 2 groups: HT (n=7; 6 men) and normotension (NT) (n=19). According to the conventional night–day systolic BP ratio >0.9, 15 individuals (8 men and 7 women) were categorized as non-dippers. Metabolomics using Nuclear Magnetic Resonance was performed on stool samples, including the quantification of the 3 main SCFAs (i.e. acetate, propionate and butyrate). Results: Multivariate analysis (principal component analyses (PCA) and partial least squares (PLS-DA)) of stool metabolomics were not able to statistically separate HT versus NT groups. However, this approach discriminated dippers versus non-dippers groups in both male and female cohorts (Q²=0.87 and 0.98, respectively), as well as in the entire cohort (Q²=0.68). As previously described, fecal amounts of acetate, propionate and butyrate were higher in HT patients than in NT patients in the entire cohort (p=0.027; p=0.015 and p=0.015, respectively). Fecal amounts of acetate, propionate and butyrate were also significantly higher in non-dippers versus dippers in the entire cohort (p=0.027; p=0.038 and p=0.036, respectively). Significant correlations between stool metabolomes and the 24h-mean BP levels were found in male and female cohorts (R²=0.63 and 0.79 respectively) as well as in the entire cohort (R²=0.54). Conclusion: In conclusion, this 26-patient cohort highlights significant correlations between stool metabolome and (i) BP levels and (ii) non-dipping BP profile in both men and women.